Phenolic Rich Fractions from Mycelium and Fruiting Body of Ganoderma lucidum Inhibit Bacterial Pathogens Mediated by Generation of Reactive Oxygen Species and Protein Leakage and Modulate Hypoxic Stress in HEK 293 Cell Line - Jigni Mishra; Anivesh Joshi; Rakhee Rajput; Kaushlesh Singh; Anju Bansal; Kshipra Misra (Hindawi Limited, 2018)
Ganoderma lucidum (G. lucidum) fungus (Family Ganodermataceae) is widely used as a traditional medicine in China, Japan, and many Asian countries on account of its numerous medicinal properties such as antioxidant, anticancer, antimicrobial, energy enhancing, and immunostimulatory. This broad spectrum of therapeutic effects exhibited by G. lucidum is ascribed to its abundance in several classes of chemical constituents, namely, carbohydrates, flavonoids, minerals, phenolics, proteins, and steroids which possess substantial bioactivities. The aim of the current study was to prepare phenolic rich fractions (PRFs) from aqueous extract of the Indian variety of G. lucidum mycelium and fruiting body. These fractions were assessed for their antioxidant capacity by TPC (total phenolic content), TFC (total flavonoid content), FRAP (ferric reducing antioxidant power), and ABTS [2,2-azino-bis(3-ethylbenzothiazoline)-6-sulfonic acid] assays. Quantification of flavonoids and nucleobases present in the fractions was carried out by high-performance thin layer chromatography (HPTLC). The antibacterial activity of the fractions was evaluated against Escherichia coli, Salmonella typhi, and Staphylococcus aureus. The antibacterial mechanism of action of the PRFs was established to be generation of reactive oxygen species and leakage of proteins within bacterial cells. Additionally, the protective effect of the PRFs in counteracting hypoxia was observed in HEK 293 cell lines.